2004
DOI: 10.1093/jee/97.3.1058
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Resistance to Transgenic Bacillus thuringiensis Poplars in Chrysomela tremulae (Coleoptera: Chrysomelidae)

Abstract: The area under genetically engineered plants producing Bacillus thuringiensis (Bt) toxins is steadily increasing. This increase has magnified the risk of alleles conferring resistance to these toxins being selected in natural populations of target insect pests. The speed at which this selection is likely to occur depends on the genetic characteristics of Bt resistance. We selected a strain of the beetle Chrysomela tremulae Fabricius on a transgenic Bt poplar clone Populus tremula L. x Populus tremuloides Michx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…In a previous investigation, we showed that an allele conferring resistance to Bt poplar in a field population of C. tremulae of the Centre region of France was segregating at a frequency of 0.0037 (Génissel et al, 2003a). We subsequently demonstrated that this resistance was completely recessive and determined by a single allele at one autosomal locus (Augustin et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In a previous investigation, we showed that an allele conferring resistance to Bt poplar in a field population of C. tremulae of the Centre region of France was segregating at a frequency of 0.0037 (Génissel et al, 2003a). We subsequently demonstrated that this resistance was completely recessive and determined by a single allele at one autosomal locus (Augustin et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…The two resistant strains, R#60 and R#116, were established from two different resistant isofemale lines selected on the foliage of a transgenic Bt poplar line producing the Cry3Aa Bt toxin (Génissel et al, 2003a). Both the R#60 and R#116 strains are fixed for a recessive allele conferring resistance to the Cry3Aa toxin (Augustin et al, 2004; Augustin, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, resistant Chrysomela tremulae beetles were found feeding on transgenic Bt poplar with a mortality similar to that of beetles fed with nontransgenic poplar leaves. Such findings call for implementation of suitable resistance-management strategies together with any release of transgenic resistant trees into nature (Génissel et al 2003, Augustin et al 2004. Generally, effects of transgenic trees on ecosystems have carefully to be evaluated (van Frankenhuizen & Breadmore 2004; see Chapter 7 of this book).…”
Section: Biological Control Of Harmful Insectsmentioning
confidence: 99%